Office management : principles and practices - Miranda, Gregorio S.; Gow, Carmelita Miranda (Mandaluyong City : National Book Store, 1994)
The office function is nothing new. in fact, it has been in existence for countless centuries and is evolving as an important phase of business administration.
CHAPTER 1. The office in today's world of business -- 2. Organizing for office operations -- 3. Office layout and working conditions -- 4. Office equipment and machines -- 5. Selection and placement -- 6. Personnel testing -- 7. Training -- 8. Office manuals -- 9. Supervising employees -- 10. Maintaining discipline -- 11. Motivating employees -- 12. Employee relations and morale -- 13. Communication in business -- 14. How to prepare business letters -- 15. Records management -- 16. Performance review and methods improvement -- 17. Health and safety in the office.
Includes bibliographical references.
Keywords: OFFICE MANAGEMENT